BAURAN PEMASARAN DAN KUALITAS LAYANAN TERHADAP LOYALITAS NASABAH MELALUI KEPUASAN NASABAH DI PT. PEGADAIAN (PERSERO) CABANG DENPASAR. - Ari, Lestawan; Wayan, Wijayanti (Jurnal Ilmiah Manajemen & Bisnis, 2017)
ABSTRACT This research aims to determine the influence of marketing mix and service quality to customer loyalty through customer satisfaction in PT Pegadaian (Persero) Denpasar branch. It used 132 samples of respondent with propotional random sampling. The data used are the primary data which obtained through questionnaires distributiion. The method for data analysis is Structural Equation Modeling (SEM) with Analysis of Moment Structure (AMOS) computer program. The result shows that all independent variables of Marketing Mix and Service Quality have a significant effect on Customer Loyalty through Customer Satisfaction.